Juozas Gabrys and Lithuania at the League of Nations: Political Activity - Šipelytė, Monika (Lietuvos istorijos studijos, 2022)
The political activity of Juozas Gabrys at the League of Nations in Geneva from 1927 to 1939 is the main subject of this article. He and his colleagues established Lithuanian Information Bureau here in the 1930s and worked as journalists. Gabrys also sought to gain a position as a Lithuanian diplomat and the best possibility for that was the post of an ambassador to the League of Nations in Geneva. He thought that his mission was to propagate Lithuanian interests in Western Europe, and the fact that he had started this activity before World War I, should have granted a good and prosperous life for himself as well. Unfortunately, good intentions not always were embodied in the fruitful results. As for the image of the Lithuanian activity in Geneva, not all of Gabrys’ actions succeeded in a positive way. Of course, at the surroundings of the League, Lithuania was seen and heard not only from Gabrys’ publications, but also from official Lithuanian information agencies and legislations. But maybe his irony and accusations worked as stimulator for other Lithuanian journalists and politicians? And maybe his true role at the scene of diplomacy was not to make the decisions, but to take into account every decision made and explain it to the society of Lithuania and Geneva.